Decomposition of Partial Fraction (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Partial Fraction Decomposition is a vital technique in mathematics used to simplify complex rational functions into more manageable components. This article serves as a detailed exploration of Partial Fraction Decomposition, covering its definition, methods, applications, and practical examples. This article delves into the concept of Partial Fraction Decomposition, a fundamental technique in algebra and calculus. It elucidates the process of simplifying rational functions by breaking them down into simpler fractions, making complex expressions more manageable.